PENGGUNAAN PACLOBUTRAZOLDAN ABA DAL AM PERBANYAKAN X NENAS SIMADU MELALUI KULTUR IN VITRO - Ragapadmi Purnamaningsih; Ika Mariska; Yati Supriati (BERITA BIOLOGI, 2009)
Pineapple (Ananas comosus L. Merr.), represents an important crop in Subang. Somaclonal variation is one of the problem to develop pineapple, especially Simadu variety. Probability to conduct Simadu progeny from the mother plant is very low (5%).Its caused by chimeric of the somatic cells that form meristem.In vitro culture is the alternative method to solve the problem by using the meristem cells from Simadu fruit as explant. Unfortunately, genetic diversity has been observed in many spesies during tissue culture.This phenomenon is usually termed somaclonal variation. Many studies on pineapple demonstrsted that some in vitro propagated materials differ from the source materials from which they are derived.To minimize genetic variability, the use of growth inhibitor such as paclobutazol and absisic acid hopefully would gave the important role in genetic stability. The aim of the research is to multiply Simadu pineapple by using tissue culture technic. In vitro shoot induce from crown of the Simadu fruit until get the sterile shoots. Combination of kinetin (0-5 ppm) with paclobutrazol ( 0-0.1 ppm) or ABA (0-1 ppm) was used in the multiplication stage. Result showed that there are no interaction between kinetin and paclobutrazol or ABA, but there is influence of the single factor. Kinetin increase leave number but decrease plant height and root number. Paclobutrazol increase shoot and leave number, but decrease plant height and root number. There is no influence of ABA to plant height, shoot and root number but decreased leaves number.